PELAKSANAAN UNDANG-UNDANG NOMOR 6 TAHUN 2014 TERKAIT FUNGSI BADAN PERMUSYAWARATAN KALURAHAN DALAM PEMBENTUKAN PRODUK HUKUM KALURAHAN SECARA PARTISIPATIF DI KALURAHAN TEGALTIRTO KEPANEWON BERBAH KABUPATEN SLEMAN - Maharsi, Ghirindra Chandra; Puri Maharani, Andina Elok (Res Publica: Jurnal Hukum Kebijakan Publik, 2023)
The study examines how the implementation of Law number 6 of 2014 related to the function of the Tegaltirto Village Consultative Body in forming participatory village law products in the Tegaltirto Village, as well as knowing the obstacles faced by the Tegaltirto Village Consultative Body in carrying out its function in forming participatory village law products in the Tegaltirto Village. . This legal research is in the form of a descriptive empirical legal research with a qualitative approach. Types and sources of research data used by the author are primary data and secondary data with data collection techniques through interviews, and retrieval of textual study information to assess secondary data. Then analyzed using data analysis techniques with a qualitative analysis model. The research was conducted at Tegaltirto Village, Kepanewon Berbah, Sleman Regency. The results show that in the process of forming the Kalurahan law product. The Tegaltirto Village Consultative Body is involved in the product of this Kalurahan Regulation in accordance with the statutory regulations. In carrying out its function, discuss and agree on the Draft Perkal. However, the Tegaltirto Village Consultative Body was not active in initiating the Village Head Regulation Draft. In accommodating and channeling the aspirations of the community, the Tegaltirto Urban Village Consultative Body is active in capturing aspirations and disseminating it to the community. So that the stipulated legal product has involved community participation. In carrying out its functions the Tegaltirto Village Consultative Body has experienced obstacles that they are aware of or not, namely: 1) The position of the Head of Tegaltirto Urban Village, which was vacant for one year; 2) Human resources of the Village Head Consultative Body; 3) The fee earned is too small; 4) No budget plots for absorption of community aspirations; 5) External factors lack of public knowledge about the existence of the Tegaltirto Village Consultative Body which is due to a lack of socialization regarding this matter.